Dynamic Control and Analysis of Dual Active Bridge Converters in Grid-Connected PV-BESS - Mehmet Can Sekanli; Samet Yalçin; Okan Bingol (Applications of Modelling and Simulation)
Rising global energy demand, along with environmental concerns over greenhouse gas emissions, has made renewable energy systems increasingly important. Integrating photovoltaic (PV) arrays with battery energy storage systems (BESS) addresses the intermittent nature of solar energy effectively. This research focuses on simulating and analyzing a grid-connected PV-BESS configuration, incorporating a Dual Active Bridge (DAB) converter. The system was modelled using MATLAB/Simulink, with specifications including a 36-kW PV array, a 162-kWh battery, and a bidirectional power capability of 18 kW. The Perturb & Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm optimized power extraction from the PV array, while the DAB converter employed Single Phase Shift (SPS) control for efficient, bidirectional energy management. Comprehensive testing across eight distinct scenarios showed reliable DC-link voltage control around 600 V and a notable reduction in inverter harmonic distortion (THD ≈ 2.5%). Overall, the simulation results confirm the robustness and practicality of the proposed design for improving grid-connected PV-BESS integration.